Aliteracy, people who can read but won't - Thimmesch, Nick.; American Enterprise Institute for Public Policy Research (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1984)
This is the proceeding of a conference Sponsored by the American Enterprise Institute for Public Policy Research (Washington, DC, September 20, 1982) . The eight papers discuss the following topics: (1) the nonreading culture, (2) aliteracy and the newspaper industry, (3) television and literacy, (4) the "reading to learn" approach, (5) books in an electronic age, (6) aliteracy and the decline of the language, (7) the magazine industry in a time of change, and (8) the role of the schools in teaching reading. The compilation includes two discussions of questions relative to these topics.
asm; 14/02/19
Loans
Keywords: Books and reading; Literacy